PERTI in Minangkabau: Social, Religious, and Educational Dynamics from Historical and Contemporary Perspectives - Riri Susanti; Fauzi Zaitul Ikhlas; Iswantir Iswantir; Rika Haida Rahma (The Future of Education Journal, 2025)
This study analyzes the historical and contemporary dynamics of the Islamic Tarbiyah Association (PERTI) as a religious organization deeply rooted in the educational tradition of the Islamic Tarbiyah Madrasah (MTI) in Minangkabau. MTI, a product of the transformation of traditional surau (Islamic prayer hall) in the early 20th century, forms the epistemological, pedagogical, and ideological foundation for PERTI. Through a qualitative approach with a historical-sociological design, this study traces the evolution of PERTI from its emergence as a consolidation of older scholars to its development as a modern organization that plays a role in the educational, social, and religious fields of society. The research findings indicate that the religious identity of Ahlussunnah wal Jama'ah and the Shafi'i school of thought, the tradition of the yellow book, and active learning methods such as munazharah and mudzakarah are the pillars of PERTI's intellectual character. Furthermore, PERTI's close relationship with the Minangkabau social structure, particularly through the adat principle of basandi syarak, syarak basandi Kitabullah, provides strong legitimacy for its social role. This study confirms that PERTI's ability to maintain tradition while adapting to the demands of modernization is key to the organization's sustainability. The results of this study contribute to enriching studies on traditional Islamic education and local religious organizations in Indonesia.